“CAN WORD WALL ASSESS STUDENTS’ WORDS?”: NURTURING INCLUSIVITY AND ADVANCEMENT IN RURAL SECONDARY EDUCATION - Aprilia, Putri Kurniawan; Mistar, Junaidi; Mustofa, Mutmainnah; Syabilla, Zalsa Febrina (University of Kuningan, 2024)
In rural areas, getting access to quality education and appropriate assessment opportunities can be challenging for students. This study seeks to bridge this educational divide by examining the viability of online platforms, particularly the Word-wall platform, as an efficient assessment tool for rural secondary school pupils. The research questions are centered on determining how students perceive the Word-wall platform and maximize its implementation to address the unique requirements and difficulties of assessing students in rural areas. This study involved students of private secondary school in rural area. This research used qualitative method with case study design, and it was utilized to obtain a comprehensive understanding of students' reactions to the Word-wall platform for English learning. Interviews for assessing students’ opinions were used to collect data. The findings indicate that students responded positively, expressing a strong desire to use the platform for future assessments, such as daily tests, quizzes, and exams. Further, student feedback highlights the significance of contextual relevance, comprehensive training, better accessibility features, and customization in addressing the unique challenges rural areas face. The results of this study tend to contribute to the growth of effective assessment practices in rural areas and provide helpful insights into applying online platforms for equal educational opportunities.